Comparative Study of Cognitive Differences in Rural Landscapes Based on Eye Movement Experiments - Yanbo Wang; Kankan Li; Jiaxin Li; Tiange Hao; Zhishu Zhou (Land)
With the booming development of rural tourism, the users of rural environments are gradually becoming more diverse. Both tourists and villagers are the main appreciators of rural landscapes, but the cognitive similarities and differences in rural landscape between the two have not yet been explored. Therefore, taking Wangshang Village, located in Shaanxi Province, China as a case study, this research used a combination of quantitative analysis (eye-tracking technology) and qualitative analysis (semi-structured interviews) to compare and analyze the cognitive similarities and differences of rural landscapes between tourists and villagers. The experimental results showed that the cognitive similarities and differences in rural landscapes between tourists and villagers are mainly reflected in their level of cognition, observation methods, and key elements of focus. The reasons for cognitive differences are due to the different living backgrounds of the two groups of subjects, as well as their varying levels of familiarity, novelty, and personal needs towards rural landscapes. In conclusion, studying the cognitive differences between the two groups of participants, tourists and villagers, can help address the homogenization problem faced by rural landscapes. Meanwhile, the results of this study also provide theoretical guidance and methodological support for rural landscape design.